2020
DOI: 10.1055/s-0040-1702157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sensation on Mastectomy Skin Flaps following Immediate Breast Reconstruction

Abstract: Background During a subcutaneous mastectomy, nerves are severed and patients lose sensation on the breast skin. The aim of this study is to investigate factors that have impact on the sensation of the mastectomy flaps and patients' own perception regarding overall breast skin sensation. Patients and Methods Patients who have undergone skin sparing or nipple sparing mastectomy with immediate reconstruction with either an implant or autologous tissue were included. Sensory assessment was performed at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
8
2
1
Order By: Relevance
“…Khan et al 13 compared immediate implant reconstructions with immediate latissimus dorsi with implant reconstructions and detected no significant difference in breast sensation between groups. Akdeniz Dogan and Farhadi 14 showed that, unlike the results of the present study, the percentage of patients in the autologous group reporting no sensation was higher in some areas compared with the implant group, which indicates better preservation of sensation in the implant group. However, the mastectomy types and radiation used in the autologous group are not clear 14 .…”
Section: Discussioncontrasting
confidence: 96%
“…Khan et al 13 compared immediate implant reconstructions with immediate latissimus dorsi with implant reconstructions and detected no significant difference in breast sensation between groups. Akdeniz Dogan and Farhadi 14 showed that, unlike the results of the present study, the percentage of patients in the autologous group reporting no sensation was higher in some areas compared with the implant group, which indicates better preservation of sensation in the implant group. However, the mastectomy types and radiation used in the autologous group are not clear 14 .…”
Section: Discussioncontrasting
confidence: 96%
“…Within autologous reconstruction, DIEP flaps recover in the most sensate manner, followed by TRAM flaps, and then LD flaps. 22 One hypothesis proposed is the delay in neural healing across the thickness of autologous flap tissue relative to implant-based reconstruction with tissue expanders. 23 This could also be explained by the improved sensation in implant-based reconstruction relative to autologous breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…20 A comparison of nipple-sparing mastectomy has shown improved light touch and pleasure sensation relative to skin-sparing mastectomy, which could lead to a reduced incidence of thermal injury in nipplesparing mastectomy relative to skin-sparing mastectomy. 21 Unfortunately, our literature review possessed limited data with regard to the type of mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, in a study of 59 breasts in 40 women, Zeynep and Farhadi demonstrated that none of the patients reported normal sensation regardless of mastectomy type (nipple sparing or skin sparing) nor demonstrated any light touch sensation. 22 Other authors advocate that the higher quality of sensibility recovery in sensate breast reconstruction outweighs the risk of additional operating time. 7 Furthermore, systematic review has demonstrated that innervated flaps do seem to lead to greater sensate recovery at an earlier stage than noninnervated flaps.…”
Section: Discussionmentioning
confidence: 99%